Iklan Xl Versi Xlalu di Televisi Terhadap Kekuatan Brand XL - Aqiel Aula; Hadi Ismanto (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2021)
The presence of print and electronic media has created a serious attitude for entrepreneurs, where they are forced to always improve product quality; goods or services they offer. Entrepreneurs not only carry out a product positioning strategy in the market through the establishment of quality standards and service quality, but they also try to maintain a brand position in the minds of consumers through strengthening promotional strategies. This research includes quantitative research, where in this study, research tries to prove empirically and quantitatively and tries to prove a significant influence between two variables, namely variables X and Y, through hypothesis testing and is a survey research, this researcher will take samples from a population that has determined by using a tool in the form of a questionnaire to collect and explore primary data from the field or a predetermined audience. Based on the research results that have been obtained, it is stated that the hypothesis of the XL Advertising version Xlalu has a significant influence on XL Brand Equity or in other words based on the hypothesis that Ha is accepted which indicates that the XL Advertising version X then affects brand equity significantly. The advertising regression coefficient is 0.490 and the coefficient of determination (KD) shows the R Square value of 0.552 or 55.20% (rounded up to 55%) of the results (r2 x 100%). This means that the variation of changes in Brand Equity is influenced by the XL version of XThen's Advertisement by 55% and the remaining 45% is influenced by other factors besides Advertising.